Five new species of Spartaeus Thorell, 1891 from China (Araneae: Salticidae) - Yang, Su-Fang; Liu, Wang; Liu, Ping; Peng, Xian-Jin (Zootaxa, 2017)
Five new species of Spartaeus Thorell, 1891 from China are described: S. forcipiformis sp. nov. (male), S. pinniformis sp. nov. (male and female), S. serratus sp. nov. (female), S. tengchongensis sp. nov. (male and female) and S. triapiculus sp. nov. (male and female). Maps with records are given.